(untitled) (World Economics and Finance Bulletin, 2023)
This article discusses ways to strengthen the integration of the banking system with the real sector of the economy through the adaptation of some elements of Islamic banking. In addition, Islamic credits and their application to Uzbekistan, many proposals and recommendations have been developed